Collaborative Learning with Students - the Relevance of Interpersonal Affordances in the Field of Assessment - Zuzanna Zbróg (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: In the introduction I explain the meaning of the main concepts and theoretical categories: a community of practice, the relational concept of learning through knowledge sharing, and social networks. I provide examples of factors that influence the effectiveness of the knowledge sharing process within communities of practice. I add to the analysed concept the category of affordances which is related to the possibilities to act in a specific environment. Research Aim: The aim of the research is to understand and describe how I create, interpret and change my social and personal environment. I formulate my research perspective in the following questions: How to use possible interpersonal affordances in the field of assessment to build a community of entities learning from each other in the academic space? Method: It is my choice to work using autoethnography, I apply the procedure of data analysis following the evocative approach, which is characterised by a change in both the subject of cognition (the researcher) and the recipient of the message. Results: The contemporary context of students' social functioning requires a decisive transition/return to the culture of relational learning, in which the following are important: taking care of emotional well-being, sensitivity to students' needs, and support, including in the form of constructive feedback based on individual or group (peer) reflection. These types of values shared in a group provide an environment conducive to learning. Conclusions: Interpersonal affordances in the field of assessment come from certain types of motivations and values that guide a person building relationships in a specific community. The crisis situation afforded me actions that involved changing my style of everyday functioning to a more attentive, supportive one, requiring the creation of a relational, comfortable space for learning. Communication relationships based on various types of constructive feedback have observably led to a positive change in the contexts of learning from each other.